Impact of hidradenitis suppurativa-specific wound dressing system on patient quality of life and dressing-related pain: pilot study. (2nd November 2022) - Moloney, Suzanne; Fitzgerald, David; Roshan, Davood; Gethin, Georgina
Abstract : Objective: It is theorised that adhesive-free wound care developed specifically for patients with hidradenitis suppurativa (HS) can improve their quality of life (QoL). Our study aimed to investigate the impact of a novel wound care device on Dermatology Life Quality Index (DLQI) scores, and other factors related to experienced pain, time spent changing dressings, comfort, ease of use and body image. Method: A 21-day, single-arm, unblinded, pilot trial was conducted to assess ease of use and the impact of effective wound care on various aspects of wound management in patients with HS. Participants were provided two trial garments and trial dressings as required, to use over a 21-day period in the home setting. A seven-item questionnaire and the DLQI questionnaire was completed on days 0, 7, 14 and 21. Results: All 15 participants were female, aged >18 years old and with a diagnosis of HS. Mean DLQI score at baseline (day 0) was 19.3, which was reduced to 4.53 on day 21, a significant improvement in 100% of participants (p<0.001). High levels of dressing-related pain, assessed using an 11-point Visual Analogue Scale, reduced from 5.53 at baseline to 0.8 on day 21. Other significant improvements in terms of patient comfort, time spent on changing dressings, body confidence and the dressing's ability to retain exudate were also noted. Conclusion: The results illustrated the improvement made to study participants' day-to-day activities and QoL when effective HS-specific wound care products were provided. Wound care is an essential component in the treatment journey of patients.